Cost-Benefit Analysis of Genetic Testing as a Prenatal Diagnostic Tool for Thalassemia: A Single-Center Study From Central Thailand - Malasai K; Jittikoon J; Udomsinprasert W; Talungchit P; Youngkong S; Sangroongruangsri S; Mahasirimongkol S; Chaikledkaew U (ClinicoEconomics and Outcomes Research)
Kwandao Malasai,1,2 Jiraphun Jittikoon,3 Wanvisa Udomsinprasert,3 Pattarawalai Talungchit,4,5 Sitaporn Youngkong,5,6 Sermsiri Sangroongruangsri,6 Surakameth Mahasirimongkol,7 Usa Chaikledkaew5,6 1Social, Economic and Administrative Pharmacy (SEAP) Graduate Program, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 2Social Pharmacy Research Unit, Faculty of Pharmacy, Mahasarakham University, Maha Sarakham, Thailand; 3Department of Biochemistry, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 4Department of Obstetrics and Gynecology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 5Mahidol University Health Technology Assessment (MUHTA) Graduate Program, Mahidol University, Bangkok, Thailand; 6Social and Administrative Pharmacy Division, Department of Pharmacy, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 7Information and Communication Technology Center, Office of the Permanent Secretary, Ministry of Public Health, Nonthaburi, ThailandCorrespondence: Usa Chaikledkaew, Social and Administrative Pharmacy Division, Department of Pharmacy, Faculty of Pharmacy, Mahidol University, 447 Sri-Ayudhaya Road, Rachathewi, Phayathai, Bangkok, 10400, Thailand, Email usa.chi@mahidol.ac.thPurpose: This study aimed to evaluate the costs and benefits of genetic testing, specifically mutation analysis and prenatal diagnostic testing, for the confirmation of thalassemia in at-risk pregnancies in Thailand, providing crucial insights to inform public health policy decision-making.Patients and Methods: We analyzed the costs and benefits of following standard screening guidelines, which included a sequence of tests such as mean corpuscular volume (MCV)/mean corpuscular hemoglobin (MCH) with dichlorophenol indophenol precipitation (DCIP), hemoglobin (Hb) typing, genetic testing, and amniocentesis. A decision-tree model was employed for this analysis. The study compared the scenarios with and without genetic testing, adopting a societal perspective that accounted for costs during pregnancy and the lifetime of a child born with thalassemia. Both one-way and probabilistic sensitivity analyses were conducted to account for uncertainties in the parameters used.Results: The results revealed that adhering to the standard screening program with genetic testing resulted in a cost-savings of approximately 490 USD per prevented thalassemia case. Among the diagnostic methods, the specificity of the MCV/MCH with DCIP showed a higher degree of sensitivity relative to other testing methods, significantly influencing the outcomes. From a governmental perspective, with a full uptake of genetic testing, the incremental budget required was estimated to be 3.7 million USD (131 million THB) for one year.Conclusion: These findings are particularly valuable for policymakers, as they provide robust evidence supporting potential revisions to the reimbursement structure within Thailand’s Universal Health Coverage benefit package, facilitating better management of thalassemia and improving prenatal care.Keywords: cost-benefit analysis, genetic testing, prenatal screening, thalassemia, pregnancy